중국 가구 제작 공정 역사적 발전 변화에 관한 연구 - 장샤오통(Xiaotong Zhang); 고정욱(Jungwook Go); 김형우(Hyungwoo Kim) (한국콘텐츠학회 논문지, 24(10), 2024)
중국 가구는 오랜 역사를 지니고 있으며, 명청(明清)시대에 "황금기"를 이루었다. 그러나 현대 가구 산업화의 영향으로 제작 공정의 표준화, 획일화에 따른 제품의 동질화가 가속화되었다. 그로 인해, 지역 문화적 고유성을 대표하는 가구의 특성은 존재감이 미약해졌다. 이에 본 연구의 목적은 중국 역사 가구 제작 공정의 발전 변화 추이를 분석하는 것으로 가구의 제작 공정에 따른 문화적 투영성을 재고하고자 한다. 이에 따라 관련 문헌과 역사자료를 귀납적인 탐색적 연구방법으로 중국 시대별 가구 제작 공정의 재료, 조립 방식, 제작 공예, 제작 도구 네 가지 측면에서 고찰하고 그 특징을 분석하였다. 이러한 시대별 제작 공정의 반복적 현상을 통찰하여 역사 가구의 발전변화를 시각화하였다. 이에 따른 연구 결과로 중국 가구 제작 공정의 역사적 발전은 재료, 조립 방식, 제작 공예, 제작 도구 측면의 활용 범주가 반복적으로 확장하며 기술적 고도화되는 추이를 나타내는 것을 알 수 있었다. 이러한 발전 추이를 통해 미래 가구 발전 방향을 예측할 수 있을 뿐만 아니라, 중국 역사 가구의 문화를 계승하고 현대 가구 디자인에 새로운 영감을 제공하는 데에도 가치를 지닌다. Chinese furniture boasts a long history, reaching its "golden age" during the Ming and Qing dynasties. However, the influence of modern industrialization in furniture production has accelerated the standardization and homogenization of manufacturing processes, leading to a diminished presence of furniture characteristics that represent regional cultural uniqueness. The purpose of this study is to analyze the developmental trajectory of Chinese historical furniture manufacturing processes and to reconsider the cultural reflection inherent in these processes. To achieve this, relevant literature and historical materials were explored using an inductive and exploratory research method. The study examines and analyzes the characteristics of Chinese furniture production across different historical periods from four perspectives: materials, assembly methods, craftsmanship, and tools. By gaining insights into the repetitive patterns of these processes over time, the study visualizes the developmental changes in historical furniture production. The results indicate that the historical development of Chinese furniture manufacturing processes is characterized by the repeated expansion and technological advancement in the utilization of materials, assembly methods, craftsmanship, and tools. Understanding this developmental trajectory not only allows for predictions about the future direction of furniture development but also holds value in preserving the cultural heritage of Chinese historical furniture and providing new inspiration for modern furniture design. KCI Citation Count: 0